Intestinal dysbiosis: a possible mechanism of alcohol-induced endotoxemia and alcoholic steatohepatitis in rats - Mutlu, Ece (2009)
BACKGROUND: Clinical and animal data indicate that gut-derived endotoxin and other luminal bacterial products are necessary cofactors for development of alcoholic liver disease (ALD). Although gut leakiness is clearly an important cause of endotoxemia in ALD, it cannot fully explain endotoxemia in all ALD subjects and thus other factors may be involved. One possible factor is a change in gut microbiota composition (dysbiosis). Thus, the aim of our study was to interrogate the gut bacterial microbiota in alcohol-fed rats to see if chronic alcohol consumption affects gut bacteria composition. METHOD: Male Sprague-Dawley rats were given either alcohol or dextrose intragastrically by gavage twice daily for up to 10 weeks. A subgroup of rats was also given either a probiotic (lactobacillus GG) or a prebiotic (oats) by gavage. Ileal and colonic mucosal-attached microbiota composition were interrogated by Length Heterogeneity PCR (LH-PCR) fingerprinting. RESULTS: Bacterial microbiota composition in alcohol-fed rats is not different from dextrose fed rats at weeks 4 and 6. Mucosa-associated microbiota composition in the colon is altered at 10 weeks of daily alcohol gavage. Both LGG and oats prevented alcohol-induced dysbiosis up to 10 weeks of alcohol treatment. CONCLUSION: Daily alcohol consumption for 10 weeks alters colonic mucosa- associated bacterial microbiota composition in rats. Our data showed, for the first time, that daily alcohol consumption can affect colonic microbiome composition and suggest that dysbiosis may be an important mechanism of alcohol-induced endotoxemia. Further studies are needed to determine how dysbiotic microbiota contributes to development of ALD and whether therapeutic interventions targeted towards dysbiotic microbiota can prevent complications of alcoholism like ALD.